Role of Notch Receptors in Hematologic Malignancies - Laura Gragnani; Serena Lorini; Silvia Marri; Anna Linda Zignego (Cells, 2020)
Notch receptors are single-pass transmembrane proteins that play a critical role in cell fate decisions and have been implicated in the regulation of many developmental processes. The human Notch family comprises of four receptors (Notch 1 to 4) and five ligands. Their signaling can regulate extremely basic cellular processes such as differentiation, proliferation and death. Notch is also involved in hematopoiesis and angiogenesis, and increasing evidence suggests that these genes are involved and frequently deregulated in several human malignancies, contributing to cell autonomous activities that may be either oncogenic or tumor suppressive. It was recently proposed that Notch signaling could play an active role in promoting and sustaining a broad spectrum of lymphoid malignancies as well as mutations in Notch family members that are present in several disorders of T- and B-cells, which could be responsible for altering the related signaling. Therefore, different Notch pathway molecules could be considered as potential therapeutic targets for hematological cancers. In this review, we will summarize and discuss compelling evidence pointing to Notch receptors as pleiotropic regulators of hematologic malignancies biology, first describing the physiological role of their signaling in T- and B-cell development and homeostasis, in order to fully understand the pathological alterations reported.